Oral delivery of encapsulated hormone for fish spawning - Xu, Qunying (Nanyang Technological University, 2023)
In response to the growing global need for fish production, this study proposes an innovative alternative to the conventional method of hormone-induced fish spawning, which currently relies on manual hormone injections, a process that introduces risks of injury, infection, and mortality. The research focuses on developing a safe and efficient oral hormone delivery system. Prior studies on oral hormone administration have demonstrated successful spawning across several fish species. However, these methods necessitate 50-125 times more hormone dosage compared to injection, due to low oral bioavailability, making such delivery impractical and no commercially available oral hormone product exists yet. The study's primary innovation is the combination of Solid Lipid Microparticles (SLMs) and an acidic modifier to encapsulate hormones. This encapsulation technology is hypothesised to protect the hormones from leaching during feeding and degradation in the fish's stomach and ensure safe delivery to the targeted receptor to stimulate spawning. The study validated its hypothesis by synthesising encapsulated hormones and subsequently evaluating them through both in vitro and in vivo analyses. The results showed negligible leakage, minimal degradation, and safe hormone release. Fish trials revealed significantly elevated sex hormone levels and successful spawning, demonstrating the efficacy of this oral administration method. This research's encapsulation strategy not only offers a promising solution to the challenges of leaching and degradation but also presents profound implications for the aquaculture industry by providing a safer, more efficient alternative to manual hormone injections, potentially enhancing the efficiency and welfare of fish spawning practices, and thereby augmenting fish production.